IMPLEMENTASI PRINSIP BAGI HASIL DAN MANAJEMEN RISIKO DALAM PRODUK-PRODUK PEMBIAYAAN PERBANKAN SYARIAH DI KOTA MALANG - Abbas Arfan; Saifullah Saifullah; Fakhruddin Fakhruddin (State Institute of Islamic Studies (IAIN) Salatiga, 2016)
The aims of this research is to determine the profit and loss sharing implementits principles on the products of sharia banking finance, the risk managementimplementation on the products of sharia banking finance and the constraints faced by sharia banking in Malang. This research used statute approach to analyze and to verify data from field research, based on fatwa DSN-MUI and regulation of Bank Indonesia. Method of data collections using questionaires, and analized by interactive analysis and descriptive-quantitative method. The result are the implementation of profit and loss sharing principles on the products of sharia finance in the form of mudlarabah and musyarakah are not well implemented as regulated in fatwa of DSNMUI. The implementation of risk management generally implemented as regulated in Bank Indonesia, but the lack of understanding and knowledge in society about its contracts are caused by the unexperienced human resources.